Effectiveness of Lemon Verbena (Cymbopogon citratus) in Oral Candidiasis: A Systematic Review - Cuenca-León K; Lima-Illescas M; Pacheco-Quito EM; Vélez-León E; Zarzuelo-Castañeda A (Dove Medical Press, 2024)
Katherine Cuenca-León,1- 3 Miriam Lima-Illescas,1,2 Edisson-Mauricio Pacheco-Quito,1,2 Eleonor Vélez-León,1,2 Aránzazu Zarzuelo-Castañeda3 1Universidad Católica de Cuenca, Facultad de Odontología, Cuenca, 010105, Ecuador; 2Grupo de Investigación: Innovación y Desarrollo Farmacéutico. Grupo de Investigación en Odontología, Facultad de Odontología, Jefatura de Investigación e Innovación, Universidad Católica de Cuenca, Cuenca, 010105, Ecuador; 3Pharmaceutical Sciences Department, University of Salamanca, Salamanca, 37007, SpainCorrespondence: Katherine Cuenca-León, Universidad Católica de Cuenca, Facultad de Odontología, Avenida de las Américas, Cuenca, 010105, Ecuador, Email kcuencal@ucacue.edu.ecAbstract: The rise of phytotherapy has enabled the utilization of various plant species for medicinal purposes, such as Cymbopogon citratus (C. citratus), providing solutions for oral pathologies, such as oral candidiasis. The PubMed, Web of Science, Scopus, and SciELO databases were searched. In vivo and in vitro studies on the action of C. citratus against oral candidiasis were included, and ROBINS-I was used to determine study quality and risk of bias. The search yielded 1922 articles, of which 10 met the inclusion criteria. Limited scientific evidence exists regarding the use of C. citratus for oral candidiasis. However, studies have indicated its potent antifungal effects. Further studies, preferably clinical trials, are necessary to confirm this effect and to enable its clinical use as a therapeutic option.Keywords: systematic review, candidiasis, oral efficacy, phytotherapy